Using Benchmark Principles as a Formative Evaluation Strategy to Build a Leadership Development Culture in the Australian Rail Industry. (September 2013) - Short, Tom; Piip, Janene; Harris, Roger
Australian organisations are concerned about the global shortage of leadership talent and the increasing mobility of leaders. At the same time, studies are raising awareness among executives of the need to develop a cohort of leaders for the future. The rail industry is one sector that has been deliberating on how leadership capability can be enhanced by putting aside organisational and/or state differences in favour of a national, harmonised approach to nurture leadership development. At a time when Australian leadership talent is in short supply, this article draws on findings from research involving six major rail organisations working in partnership with universities within an Australian Government Cooperative Research Centre (CRC). The article finds that leadership development programs within the industry are infrequent, undervalued and under-resourced. It highlights the critical importance of gaining executive commitment, and develops a formative evaluation tool of 10 principles and evaluation criteria forming observable, measurable and evidence-based standards that can be appraised at the start of leadership development initiatives and programs and monitored as they unfold. The article illustrates how engaging executives in a 'formative evaluation' process before embarking on leadership development initiatives has the potential to promote successful and sustainable programs.